Fantasy, Neoliberalism and Precariousness : Coping Strategies in the Cultural Industries. - Vachet, Jérémy (Digital Activism and Society: Politics, Economy and Culture in Network Communication Ser., 2022)
Contributing to debates within cultural studies, sociology and the political economy of communication about working lives in the cultural and creative industries, Vachet answers to-date unexplored questions around the psychosocial impact of precariousness and other problematic features of work in the cultural industries.